Assessment of Particulate Matter (PM2.5) in Higher Education Facilities in the Public and Private Sectors in Karachi, Pakistan - Kamran-ul-Haq Khan; Syed Muhammad Fazal-ul-Karim; Faisal Rasheed Yazdanie; Irwanto Irwanto (Journal of Research in Environmental and Science Education, 2026)
Air pollution in educational institutions is an emerging issue since students spend a considerable amount of their time in classrooms where they are exposed to fine particulate matter (PM2.5), which may have negative health and learning effects. In most urban and industrial areas, schools/universities are the direct sufferers of the pollution sources around them, and thus form a major area of concern as far as air quality evaluation is concerned. The purpose of this report is to assess PM2.5 levels in higher educational institutes in Karachi, with the aim of highlighting the degree of exposure and its health consequences on students and the need to raise awareness among both students and among both students and relevant authorities. The experimental data on the concentrations of PM2.5 were observed in two higher educational institutions (HEI) in Karachi. This is carried out by monitoring the air quality inside and outside of three different classrooms at different time intervals with a random number of students. The measured data were subsequently compared across the sites to determine the differences in the level of pollution and to determine the degree of exposure in comparison to international air quality guidelines. This study indicated that the quality of air in private institutes is much better than that in public sector institutes, but the overall air quality is not at the level as per WHO guidelines due to the general quality of air in the city. This study recommended that the elevated level of air pollution needs urgent attention from the government and other departments responsible for maintaining a sustainable environment in the city, as it is not only harmful to the residents of the city but also creates adverse effects on the students’ health.